SINTESIS DAN KARAKTERISASI MEMBRAN ANTIBIOFOULING KOMPOSIT POLIETERSULFON/ KITOSAN/ AMMONIUM KLORIDA - Marthini, - (2020)
The accumulation of microorganisms on the filtration membrane cause the phenomenon of biofouling. In this study, chitosan and ammonium chloride (NH4Cl) as antibacterial agents were added to the polyethersulfone composite membrane (PES) to improve the antibiofouling properties of the membrane. This research methods included preparation, characterization, and composite membrane antibiofouling assay. The PES membrane was synthesized using the phase inversion method in DMAC solvent, then immersed (coating) in a CS / NH4Cl solution to form a composite membrane. The antibiofouling assay was conducted using inhibition ring method (Kirby Bauer) and Total Plate Counting (TPC) against Staphylococcus aureus and Escherichia coli. The Characterization of structure, morphology and mechanical properties of composite membranes was carried out using FTIR spectroscopy, SEM-EDX, measurement of porosity and hydrophilicity, and tensile strength test. FTIR spectra showed new absorption peak and shift in wavenumber through alkyl, hydroxyl and amine groups of chitosan due to the addition of CS/NH4Cl to the PES membrane and the percentage of chlorine in EDX shows the interaction between PES, CS, and NH4Cl on the composite membrane. The results showed the addition of NH4Cl increased the antibiofouling properties of the composite membrane, where the minimum inhibitory concentration (MIC) of the composite membrane was appeared at 200 ppm against S.aureus and E. coli. Antibiofouling activity the composite membrane increased with increasing NH4Cl concentration, where the maximum %BKR up to 99.18% and 83.33% (MA-500) for S.aureus and E.coli, respectively. The addition of CS / NH4Cl not only changed the morphological structure of the PES membrane as shown in the SEM image, but also increased the hydrophilicity (CA = 82.3o to 64.4o), increased porosity (49.63% to 70%) and the mechanical properties of membrane (0.57 MPa to 8.7 MPa).